Stamped : racism, antiracism, and you - Kendi, Ibram X.; Ibam, X. Kendi (Little, Brown and Company, 2020)
"A history of racist and antiracist ideas in America, from their roots in Europe until today, adapted from the National Book Award winner Stamped from the Beginning"--